IMPLEMENTATION OF INQUIRY LEARNING MODELS INTEGRATED WITH NESTED TO INCREASE STUDENTS CRITICAL THINKING SKILLS ON ELECTROLYTE AND NON-ELECTROLYTE SOLUTION MATERIALS - Anis Fadlilah; Harun Nasrudin (Universitas Negeri Surabaya, 2020)
This research purpose to describe the implementation of inquiry learning integrated by Nested, students' activities, critical thinking skills and student learning outcomes after the implementation of learning models on electrolyte and non-electrolyte solution materials. The research design used is